TECHNICAL UNIVERSITY IN INFORMATIVE EPOCH: THE PROBLEM Of AUTONOMY (SOCIAL-PHILOSOPHICAL ANALYSIS) - Ченбай, Н. А. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
In the article is accented attention on the features of realization of idea of autonomy of universities in an informative epoch